Meningkatkan Hasil Belajar Bahasa Inggris Melalui Model Group Investigation Siswa Kelas X IPS 3 SMA Negeri 14 Pekanbaru Tahun 2019 - Kesuma Hastuti (Journal on Education, 2022)
Based on the teacher's direct experience when teaching and also the results of the daily tests of Class X IPS 3 SMA NEGERI 14 Pekanbaru in English learning activities, it shows that student learning outcomes are still very low. Group Investigation and it is hoped that students can easily understand English learning material so that more students achieve mastery. This research aims to: 1). Improving student learning outcomes of Class X IPS 3 in the material for the English learning process using Group Investigation, 2). Increase understanding of English learning material for Class X IPS 3, and 3). Improving student learning readiness in learning English Class X IPS 3. The location of this study was at SMA NEGERI 14 Pekanbaru with a total of 36 students, 24 female students and 12 male students. The data in this study were obtained from the results of action observations and evaluation results. This research was conducted in two cycles. Each cycle is carried out based on the stages: (1) preparing an activity plan, (2) carrying out actions, (3) observing, and (4) analyzing followed by reflection. The results showed that the results of observations in the pre-action were that students in learning were less active, easily bored, and their learning outcomes were still low. In the first cycle of action, the learning activities of students who got very good and good scores were 51.39%, increasing to 95.83% in cycle II. The assessment of the work portfolio of the cycle I group was 45.83%, increasing to 91.67% in cycle II. Assessment of work results (post-test), 19.44% of students who complete increased to 88.89%. Based on the results of the research above, it can be concluded that learning using Group Investgation can improve student learning outcomes/achievements.